Assessment of Indoor Radon Exposure Affecting Lung cancer Risks in Muang District, Yala Province - Pisapak, Pattama (YRU Journal of Science and Technology, 2022)
Indoor radon concentration was measured in Muang district, Yala province, by using a solid state nuclear track detector (SSNTDs; CR-39). The suitable etching condition can be used for producing tracks in water bath, with 100 min etching in 6.25 Mol/L of NaOH at 85๐ C. A total of 30 indoor and detectors ware set for 40 days. The results of indoor radon concentration ranged from 20.70 ± 3.44 Bq/m3 to 24.57 ± 6.30 Bq/m3, which the average value of 22.63 ± 1.74 Bq/m3. The highest of indoor radon concentration found that in Lam Mai sub-district and the lowest obtained in Budi sub-district. Forthermore, the present values of the average excess lifetime cancer risk (ELCR; 0.22%) for all detectors were lower than the recommend by US EPA of 1.3 %. According to the ELCR and risk of lung cancer estimated from 30 dwellings surveyed, It is found that the lung cancer cases per year per million person (LLC) was estimated to be 10, which is lower than the limit range of 170-230 per million persons recommended by ICRP.